Perception of facial appearance and profile among Bangladeshi Laypersons (Bangladesh Journal of Medical Science, 2018)
Background: Enlightening facial esthetic is reflecting as one of the main influences in orthodontic treatment during establishing of ideal occlusion.Method: In present study, a determination was made to subsidize to the existing pool of information on the soft-tissue profile and facial awareness. Main aim of the study is to investigate how the Bangladeshi laypersons are aware of their own faces by analyzing the data collected through a structured questionnaire.Result: This study involved total 200 Bangladeshi Individuals age ranged 19 to 23 years old. A validated structured questionnaire was used to assess subjects’ evaluation of their own facial appearance. The mean awareness score for the subjects of Bangladeshi individuals ranged from 1.4 to 2.3 in male and from 1.7 to 1.9 in female for the overall impressions and from 1.3 to 2.1 in male and from 1.2 to 2.3 in female for the facial parts. Satisfaction score for the 9 items out of 24 items differed significantly between Bangladeshi female and male. An average profile of the jaw and lips are desired over more retrusive or protrusive profiles among Bangladeshi laypersons.Conclusion: It can be determined that Bangladeshi laypersons are adept to understand their own faces in the various commands and most of the peoples are worry about their profile in their everyday survives. We must evaluate our existing data to find orthodontic standards that are valid for specific ethnic groups.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.638-643